Study of crack identification methods for underwater structures based on alternating electromagnetic fields - Lou, Min; Wu, Bin; Jiang, Zhilong; Wang, Yangyang; Han, Yu (Ocean engineering, 2026)
With the expansion of offshore oil and gas operations into deeper marine environments, the harsh conditions of the deep sea demand high standards of safety and operational reliability for subsea exploration and production systems. To overcome existing limitations—namely, insufficient crack detection precision and the absence of sustained underwater monitoring—this study introduces a theoretical framework for detecting underwater cracks using alternating electromagnetic induction. A new signal inversion algorithm is developed to estimate crack geometry, alongside the creation of specialized underwater detection and flexible monitoring probes. This integrated system enables both high-precision crack identification and continuous structural monitoring. The approach is validated through a combination of numerical modeling, laboratory testing, and field deployments in the Bohai Sea. Results demonstrate a detection resolution as fine as 2 mm × 1 mm, with accuracies of 94 % for crack length and 92.5 % for depth estimation. Monitoring performance further shows recognition accuracies exceeding 91.4 % and 92 % for various crack dimensions, confirming the method's strong applicability to long-term structural health monitoring in subsea infrastructure. •Proposes an alternating electromagnetic induction method for underwater crack detection.•Develops a signal inversion algorithm to quantify crack length and depth.•Designs underwater probes and flexible devices for continuous subsea deployment.•Achieves 2 × 1 mm detection with 94 % length and 92.5 % depth accuracy.•Reaches over 91 % recognition accuracy in Bohai Sea field trials.